STRUCTURAL CHANGES IN EPINEURIUM OF RAT’S SCIATIC NERVE INFLUENCED BY HIGH-FREQUENCY ELECTROSURGICAL TECHNOLOGIES - Korsak, A. (World of Medicine and Biology, 2015)
High-frequency electrosurgical devices are widely used in modern medicine. Both with this, electrosurgical devices in welding mode can be useful in neurosurgery for quick and bloodless tissues processing, but lack of data about their influence on nervous system organs restricts their usage in clinical practice. The aim of current study was to evaluate structural changes in epineurium influenced by devices based on high-frequency electrosurgical technologies principles In current study we performed an experiment on 30 mature Wistar rats. We compared epineurium morphological features after direct electrosurgical high-frequency bipolar devices influence on sciatic nerve in cautery mode with similar device exposure in welding mode. All operations performed under thiopentone anesthesia. For operation performing we used especially designed bipolar forceps attached to high-frequency electrosurgical devices EKVZ-300 (Patonmed, Ukraine) for bipolar welding group and EKONT-0201 (Contact, Ukraine) for bipolar cautery group. In Sham operated group right sciatic nerve only was exposured without any further actions. Material for light microscopy was harvested directly after exposure and 1, 6, 12 weeks postoperatively and histological examination was performed on semithin sections. After electrosurgical device application in bipolar welding mode on sciatic nerve we revealed local protein denaturation and “gluing effect” that result in nercotic masses absence and repair processes predominance over the alteration at all postoperative terms and makes epineurium to heal more quickly. All this provides opportunities and conditions for strong epineurium connection if it is damaged. In contrast, after electrosurgical device application in bipolar cautery mode we revealed comparatively greater amount of damaged structures and delayed epineurium healing, that in our point of view, cannot provide adequate conditions for reliable tissues connection. We conclude that high-frequency electrosurgical devices in bipolar welding mode application results in epineurium continuity restoration that makes such method perspective for application in clinical practice as sutureless tissue connection technique.